Efficacy of the cross-union protocol in the treatment of congenital tibial pseudarthrosis: a comparative study - Yanhui Jing; Dahui Wang; Chunxing Wu; Zhiqiang Zhang; Yueqiang Mo; Bo Ning (BMC Musculoskeletal Disorders)
Abstract Background Congenital Pseudarthrosis of the Tibia (CPT) is a rare pediatric condition presenting substantial challenges for orthopedic surgeons. Aiming to achieve bone union, with subsequent complications such as refractures being common. The aim of the present study is to evaluate the results of our intentional cross-union protocol and to compare these outcomes with those obtained from our previously used techniques. Materials and methods Sixteen patients, with a mean age of 4.8 years (range: 1-13.3 years), who were treated with the intentional cross-union protocol were included in Group (A) Eleven patients, with a mean age of 3.5 years (range: 1.3–7.6 years), who primarily underwent intramedullary rodding with bone graft, were included in Group (B) The intentional cross-union protocol involved cross-union of the tibia and fibula, autogenous iliac bone grafting, and the insertion of bone morphogenetic protein 2 (BMP-2) aimed at achieving tibia-fibula cross-union. Retrospective evaluation of serial radiographs was conducted, and the outcomes regarding union and any subsequent complications were analyzed. Results A total of 27 patients with CPT were included in the study. All 16 patients (100%) in Group A successfully achieved primary union. Among the 11 patients in Group B, only 4 cases achieved primary union, with a primary healing rate of 36.4%. Seven cases with delayed healing required 2–4 revision surgeries for final healing. The time to union was significantly shorter in Group A (3.37 ± 0.64 months) compared to Group B (8.67 ± 3.0 months). The cross-sectional area of union was also significantly larger in Group A (6.71 ± 0.58 cm²) compared to Group B (1.18 ± 0.19 cm²). In Group A, there were no cases of refracture, whereas in Group B, 7 cases (77.8%) experienced refracture, indicating a statistically significant difference. Conclusions Our study demonstrates that the Cross-union protocol is highly effective for achieving union and preventing refracture in CPT. With such significant improvement, it has notably altered the prognosis of this challenging condition. Level of evidence IV.